DERRIDA, J. (2021), Hospitalité. Volume I. Séminaire (1995-1996), Paris. Seuil. - Carrión Murcia, Pedro (Daimon Revista Internacional de Filosofia, 2024)
Reseña de DERRIDA, J. (2021), Hospitalité. Volume I. Séminaire (1995-1996), Paris. Seuil.